Clinical, biochemical, and genetic spectrum of seven patients with NFU1 deficiency - Ahting, Uwe; Mayr, Johannes A.; Vanlander, Arnaud V.; Hardy, Steven A.; Santra, Saikat; Makowski, Christine; Alston, Charlotte L.; Zimmermann, Franz A.; Abela, Lucia; Plecko, Barbara; Rohrbach, Marianne; Spranger, Stephanie; et al. (Frontiers in Genetics, 2015)
Disorders of the mitochondrial energy metabolism are clinically and genetically heterogeneous. An increasingly recognized subgroup is caused by defective mitochondrial iron-sulfur (Fe-S) cluster biosynthesis, with defects in 13 genes being linked to human disease to date. Mutations in three of them, NFU1, BOLA3, and IBA57 affect the assembly of mitochondrial [4Fe-4S] proteins leading to an impairment of diverse mitochondrial metabolic pathways and ATP production. Patients with defects in these three genes present with lactic acidosis, hyperglycinemia, and reduced activities of respiratory chain complexes I and II, the four lipoic acid-dependent 2-oxoacid dehydrogenases, and the glycine cleavage system (GCS). To date, 5 different NFU1 pathogenic variants have been reported in 15 patients from 12 families. We report on 7 new patients from 5 families carrying compound heterozygous or homozygous pathogenic NFU1 mutations identified by candidate gene screening and exome sequencing. 6 out of 8 different disease alleles were novel and functional studies were performed to support the pathogenicity of 5 of them. Characteristic clinical features included fatal infantile encephalopathy and pulmonary hypertension leading to death within the first 6 months of life in 6 out of 7 patients. Laboratory investigations revealed combined defects of PDHc (5 out of 5) and respiratory chain complexes I and II+III (4 out of 5) in skeletal muscle and/or fibroblasts as well as elevated lactate (5 out of 6) and glycine levels (7 out of 7). Our study adds to the definition of the phenotypic spectrum associated with NFU1 mutations and might contribute to the diagnostic workup of future patients